Particle Swarm Optimization techniques for optimal location and sizing of thyristor controlled series capacitor - Jumaat, S.A.; Musirin, I.; Othman, M.M.; Mokhlis, Hazlie (2012)
One of the disturbances experienced by the power system is increase in loading condition, which often led the system to no longer remains in secure operating region. When the power system is exposed to any kind of time delay and inaccessibility of control scheme, system may become inconsistent leading to uncontrolled condition. Under this condition, the main purpose of the operator is to execute control actions to get the system back into the secure operating regions. Flexible AC transmission system (FACTS) device is one of the devices, which can be inserting to control power system stability improvement. This paper describes the optimal placement and sizing of TCSC using on Particle Swarm Optimization (PSO) method. The objective function for this study is to minimize the transmission loss, increase the voltage profile, while considering the cost of installation. Effect of weight coefficient and effect of population size during the optimization process towards obtaining the solution is also explored. To validate the proposed techniques, simulations are performed on an IEEE 30-bus system.